Exploring streotypical challenges faced by working single mothers - Rahman, Noor Watee; Abdullah, Haslinda (Sutton: Institute for Advanced Publications, 2018)
The current stigmata associated with the title single mother, which encompasses the widowed, divorcees or those who are separated, is one of the major obstacles faced by single mothers towards achieving equality with that of married women. Their role in society has been devalued considering the limited of financial, status, health, and educational background. By investigating the stererotype threats as one of the negative thinking that affect the working single mother’s mind in order to deliver their best potential for their family and children. This study aims to identify the challenges faced by working Malay single mothers in the context of cultural, values and norms of the Malay society as well as delineates the means of changing the mindset of the Malay society towards them so as to allow them to succeed in life. The differences between the Western and Asian aspects of issues will be examined and interpreted in the current context. An integrated approach that combines Role theory, Conservation Resources Theory and Social Identity Theory will be used to posit the possible factors that contribute to the elevated sterotypical challenges and threats faced by working Malay single mothers.